2022
DOI: 10.22219/raden.v2i2.20035
|View full text |Cite
|
Sign up to set email alerts
|

Online learning videos to develop creative thinking skills of students

Abstract: Creative thinking skills are 21st Century Skills which are difficult to improve when online learning is implemented. This study aimed to develop online learning videos to improve students' creative thinking skills. The product development process includes problem analysis, material collection, product design, expert test, limited trial, design revision, usage trial, and product revision. The material and design determine the feasibility of the product. Aspects of material assessment include conformity to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
3
0
4
Order By: Relevance
“…Salah satu media yang sederhana namun bisa memberikan motivasi pada siswa adalah media video. Belajar menggunakan media video akan meningkatkan perhatian dan motivasi siswa pada topik yang dipelajari (Hendriyani et al, 2022;Izzudin et al, 2013;Varisa & Fikri, 2022).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Salah satu media yang sederhana namun bisa memberikan motivasi pada siswa adalah media video. Belajar menggunakan media video akan meningkatkan perhatian dan motivasi siswa pada topik yang dipelajari (Hendriyani et al, 2022;Izzudin et al, 2013;Varisa & Fikri, 2022).…”
Section: Pendahuluanunclassified
“…Menggunakan video di kelas adalah ide yang menarik untuk dilakukan dalam pembelajaran (Hendriyani et al, 2022;Ijaz et al, 2017;Izzudin et al, 2013;Varisa & Fikri, 2022). Hal ini tidak hanya memberi guru berbagai manfaat luar biasa, tetapi juga merupakan eksperimen yang menyenangkan bagi anak-anak dan mereka pasti akan menghargai seluruh pengalaman sejak awal hingga akhir proses pembelajaran.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…The advantage of the PBL model compared to other learning models in improving creative thinking is that when students are given problems, then they are asked to obtain interactive, active learning model solutions. Other studies conducted by (Nur et al, 2020) using ERcORE, while Nur Zakiyah et al (2024, (Pasaribu et al, 2023) using STEM learning, Supratman et al (2020Supratman et al ( , 2021 using POPBL, online learning using video Hendriyani et al (2022) to promote students' creative thinking in biology learning.…”
Section: Introductionmentioning
confidence: 99%
“…Makruf et al [5] concluded that Moodle was less optimal in the implementation and evaluation of learning in higher education. Hendriyani et al [6] developed online learning videos to improve students' creative thinking skills. Bauk [7] discussed the benefits and challenges of international virtual exchange in teaching and learning at higher education institutions.…”
Section: Introductionmentioning
confidence: 99%